2018
DOI: 10.1007/s11031-018-9709-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotional contrast and psychological function impact response inhibition to threatening faces

Abstract: Poor inhibitory control over negative emotional information has been identified as a possible contributor to affective disorders, but the distinct effects of emotional contrast and fearful versus angry faces on response inhibition remain unknown. In the present study, young adults completed an emotional go/no-go task involving happy, neutral, and either fearful or angry faces. Results did not reveal differences in accuracy or speed between angry and fearful face conditions. However, responses were slower and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…On the one hand, some authors reported very low rates of commission errors, ranging from 3–4% (Shafritz et al, 2006) to about 10% (Hare et al, 2005). On the other hand, other works reported a rate of commission errors similar to the present study, that is, ranging from 20% to 25% (Greif & Waring, 2018; Roberts et al, 2013; Schulz et al, 2007). At present, the reasons for such discrepancies in the performance are unclear.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the one hand, some authors reported very low rates of commission errors, ranging from 3–4% (Shafritz et al, 2006) to about 10% (Hare et al, 2005). On the other hand, other works reported a rate of commission errors similar to the present study, that is, ranging from 20% to 25% (Greif & Waring, 2018; Roberts et al, 2013; Schulz et al, 2007). At present, the reasons for such discrepancies in the performance are unclear.…”
Section: Discussionsupporting
confidence: 87%
“…Still, Schel and Crone (2013) showed that fearful faces impaired inhibitory control with respect to neutral faces. Finally, Greif and Waring (2018) did not find differences in accuracy in No-go trials between angry and fearful faces, but they found that when the Go-signal was a happy face, angry and fearful faces decreased inhibitory control with respect to when the Go-signal was a neutral face. All in all, such investigations did not allow to draw firm conclusions about the effect of emotion on inhibition.…”
Section: The Impact Of Emotional Expressions On Inhibitionmentioning
confidence: 88%
“…The final sample included 44 younger adults (20 female, 24 male; age: M = 19.00, SD = 1.14, range 18–22; yrs edu: M = 12.70, SD = 1.00, range 12–15). Different analyses on a portion of the data for 39 of the younger adults are reported in Greif and Waring (2018). 39 older adults were recruited from the St. Louis community (20 female, 19 male; age: M = 70.18, SD = 7.39, range 60–89; yrs edu: M = 16.00, SD = 2.21, range 12–20).…”
Section: Methodsmentioning
confidence: 99%
“…In light of documented age differences in mood and anxiety (Machado et al, 2018) and in use of emotion regulation strategies (Urry and Gross, 2010), participants also completed self-report measures including the Emotion Regulation Questionnaire (ERQ; Gross and John, 2003), Spielberger State-Trait Anxiety Inventory (STAI; Spielberger and Gorsuch, 1983), and a depression inventory [older adults: Geriatric Depression Scale 30-item version (GDS; Yesavage et al, 1983); younger adults: Beck Depression Inventory (BDI; Beck et al, 1961)] to explore the possibility of differing relationships between these measures and emotional response inhibition as a function of aging. Following from our and others’ prior findings in younger adult samples (Mogg and Bradley, 2005; Pacheco-Unguetti et al, 2012; Greif and Waring, 2018), we explored whether higher anxiety or depression corresponded with poorer task performance (slower responses, more false alarms). Some measures were not administered to a small group of pilot participants during protocol development period (Trail Making Test: 2 younger adults, 4 older adults; ERQ and GDS: 1 older adult each).…”
Section: Methodsmentioning
confidence: 99%